PENGELOLAAN BADAN USAHA MILIK NAGARI (BUM NAGARI) DI NAGARI SUNGAI KAMUYANG KECAMATAN LUAK KABUPATEN LIMAPULUH KOTA - Asyatul, Elsy (journal of residu, 2019)
This research was conducted to find out how the existing management from the beginning of the planning to the implementation then how the evaluation was carried out in the management of BUM Nagari. This study uses descriptive qualitative. The research informant technique used purposive sampling. Techniques for collecting data on observations, interviews, and documentation. Based on the results of interviews, the management of BUM Nagari Sungai Kamuyang did not work based on initial planning. The management of BUM Nagari Sungai Kamuyang is ineffective because of the lack of professional managers in their fields, and a lack of public understanding of BUM Nagari